Pendidikan Inklusif Gender sebagai Upaya Pencegahan Kekerasan Seksual di Pondok Pesantren - Oktaviani, Indah; Elanda, Yelly; Alie, Azizah; Prastiyo, Endri Bagus (Sociology Department Of Syiah Kuala University, 2024)
This study aims to address two primary questions: Why does sexual violence occur in Islamic boarding schools (pondok pesantren)? How can sexual violence in these institutions be prevented? The methodology employed is a literature review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The data collection process involves four stages, starting with inclusion and exclusion criteria using Google Scholar with keywords such as Sexual Violence in Islamic Boarding Schools and Inclusive and Gender-Responsive Education in Islamic Boarding Schools. The findings reveal that the root causes of sexual violence in Islamic boarding schools are the hierarchical relationship between the kiai (religious leader) and the santri (students), the perpetuation of patriarchal culture, and the total obedience of the santri to the kiai. These factors also contribute to the underreporting of sexual violence cases, as victims and their families often feel intimidated. To address this issue, gender-inclusive education is necessary, manifested through a Gender Equality Curriculum (KKG). This curriculum ensures that all components involved in the educational system adopt gender-responsive thinking and behavior based on justice and gender equality. Gender-inclusive education will also create a non-segregated learning environment.AbstrakPenelitian ini bertujuan untuk menjawab dua pertanyaan utama: Mengapa kekerasan seksual di pondok pesantren bisa terjadi? Bagaimana upaya pencegahan kekerasan seksual di pondok pesantren? Metode yang digunakan adalah studi literatur berdasarkan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Proses pengumpulan data melibatkan empat tahapan, mulai dari tahap inklusi dan eksklusi menggunakan mesin pencarian Google Scholar dengan kata kunci Kekerasan Seksual di pondok pesantren dan Pendidikan Inklusif dan Responsif Gender di pondok pesantren. Hasil penelitian menunjukkan bahwa akar masalah kekerasan seksual di pondok pesantren disebabkan oleh adanya hierarki antara kiai dan santri, pelanggengan budaya patriarki, dan kepatuhan total santri kepada kiai. Ketiga faktor ini juga menyebabkan kasus kekerasan seksual di pondok pesantren jarang dilaporkan karena korban dan keluarganya merasa takut. Untuk mengatasi hal tersebut, diperlukan pendidikan inklusif gender yang termanifestasi melalui kurikulum kesetaraan gender (KKG). Dengan adanya kurikulum ini, semua komponen dalam sistem pendidikan akan memiliki pola pikir dan perilaku yang responsif gender, berbasis keadilan dan kesetaraan gender. Pendidikan inklusif gender juga akan menciptakan sistem pembelajaran yang non-segregasi gender.